Green titanium-based composite anode, its preparation method and application in electrochemical preparation of high-purity manganese

CN122649034APending Publication Date: 2026-08-28XIAN TAIJIN NEW ENERGY & MATERIALS SCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611064111.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

虽然传统的钛基二氧化锰电极具有上述的多项优点,但其仍存在一定缺陷,比如:电解使用槽压高、电积锰体系条件下服役寿命短、活性层在钛基材上的附着力低、易剥落

Benefits of technology

[0014]The beneficial effects of this invention are as follows: Compared with the prior art, the titanium-based composite anode of this invention consists of, from the inside out, a titanium substrate (Ti), an antimony tin oxide (ATO) underlayer, a BDD@manganese dioxide composite active layer, and a silicon isolation layer. The antimony tin oxide underlayer primarily serves two purposes: first, to improve the adhesion between the active layer and the substrate; and second, to prevent corrosion and passivation of the titanium substrate. The BDD@manganese dioxide composite active layer mainly aims to improve the oxygen evolution activity of the anode active layer, thereby reducing the anode working tank pressure. The silicon isolation layer primarily reduces corrosion of the active layer and prevents manganese dioxide deposition in the solution, maintaining electrode activity. The titanium-based composite anode improves the conductivity of the anode product, extends its service life, avoids lead contamination, and features a simple, easy-to-implement, and cost-effective manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122649034A_ABST
    Figure CN122649034A_ABST
Patent Text Reader

Abstract

The application discloses a green titanium-based composite anode, a preparation method thereof and application of the titanium-based composite anode in electrochemical preparation of high-purity manganese, and relates to the field of electrochemical preparation of high-purity manganese. The titanium-based composite anode comprises a titanium base material, and from inside to outside on the surface of the titanium base material, there are successively an antimony tin oxide bottom layer, a BDD (boron-doped diamond) and manganese dioxide composite active layer and a silicon isolation layer. The antimony tin oxide bottom layer is deposited on the surface of the titanium base material; the BDD and manganese dioxide composite active layer is prepared on the antimony tin oxide bottom layer; and the silicon isolation layer is prepared on the active layer. In electrochemical preparation of high-purity manganese, the titanium-based composite anode is used as an anode. The titanium-based composite anode (Ti / ATO / BDD@MnO2 / SiO2) not only avoids the introduction of lead pollution, but also has excellent electrocatalytic activity; in electrochemical preparation of high-purity manganese, the titanium-based composite anode solves the corrosion problem of a traditional lead anode in electrodeposition, prolongs the service life, and improves the purity of the manganese and the electrodeposition current efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical preparation of high-purity manganese, and more specifically to a green titanium-based composite anode, its preparation method, and its application in the electrochemical preparation of high-purity manganese. Background Technology

[0002] The electrolytic manganese industry is currently at a critical juncture in its transformation towards green and efficient manufacturing, facing the triple challenges of energy conservation and emission reduction, environmental pressure, and product upgrading. As one of the core pieces of equipment in this transformation process, the demand for titanium anodes is shifting from basic corrosion resistance to higher-level high efficiency and long-life catalytic performance. Traditional lead-based (or lead-silver) anodes are unstable in strongly acidic, high-current-density electrolytes, gradually corroding and dissolving, producing large amounts of lead-containing anode sludge. This not only causes environmental pollution, but also places a heavy burden on enterprises in disposing of this hazardous waste. Titanium anodes themselves do not contain lead and are extremely stable during electrolysis, without producing lead-containing anode sludge. This fundamentally solves the problem of lead contamination of electrolytes and products, representing a crucial step towards clean production. Therefore, researchers have attempted to use titanium anodes to prepare high-purity manganese. Titanium-based manganese dioxide electrodes are currently recognized as having significant advantages. When electrolyzed in aqueous solutions, titanium-based manganese dioxide electrodes exhibit good corrosion resistance, high conductivity, and the ability to handle large currents, making them suitable for the electrochemical preparation of high-purity manganese. While traditional titanium-based manganese dioxide electrodes possess many advantages, they still have certain drawbacks, such as high cell voltage during electrolysis, short service life under electrowinning manganese systems, and low adhesion of the active layer to the titanium substrate, making it prone to peeling. Therefore, the development of green titanium-based composite anodes has become a research hotspot in the field of electrochemical preparation of high-purity manganese. Summary of the Invention

[0003] To address the shortcomings of existing technologies, the present invention aims to provide a green titanium-based composite anode and its preparation method, which can be used for the electrochemical preparation of high-purity manganese anodes. By adding a tin-antimony oxide underlayer, the bonding force between the BDD@MnO2 composite active layer and the substrate is improved. The BDD@MnO2 composite active layer is used to improve the conductivity of the active layer, reduce the working tank voltage of the anode, and extend its service life.

[0004] The technical solution adopted by the present invention to solve the technical problem is: a green titanium-based composite anode, comprising a titanium substrate, wherein from the inside to the outside of the titanium substrate are a tin-antimony oxide bottom layer, a BDD@manganese dioxide composite active layer and a silicon isolation layer; the active layer comprises two active substances, BDD and manganese dioxide.

[0005] Furthermore, the thickness of the tin-antimony oxide underlayer is 0.5~4μm; the thickness of the silicon isolation layer is 4~20μm.

[0006] This invention also discloses a method for preparing a green titanium-based composite anode, comprising the following steps: Step 1) Perform surface treatment on the titanium substrate; Step 2) Deposit a tin-antimony oxide underlayer on the titanium substrate surface after the treatment in Step 1); Step 3) Prepare a BDD@manganese dioxide composite active layer on the tin-antimony oxide substrate prepared in Step 2); Step 4) Prepare a silicon isolation layer on the BDD@manganese dioxide composite active layer prepared in step 3).

[0007] Furthermore, in step 1), a laser is used to treat the surface of the titanium substrate to make the surface of the titanium substrate uniform and free of oxide scale.

[0008] Further, in step 2), a tin-antimony oxide underlayer is prepared by vacuum deposition; the vacuum deposition method is either vacuum evaporation or magnetron sputtering.

[0009] Further, in step 3), a BDD@manganese dioxide composite active layer is prepared by spraying BDD and manganese-based precursors; wherein, spraying is performed once, sintering is performed once, and spraying and sintering are repeated multiple times until the required thickness of the BDD@manganese dioxide composite active layer is achieved.

[0010] Furthermore, in step 3), a manganese nitrate solution containing BDD is used as a precursor, sprayed and dried at a temperature of 80~150℃, and then sintered at 200~450℃ for 15~60 min; the spraying method is two-fluid spraying or roller coating.

[0011] Further, in step 4), a silicon isolation layer is prepared on the BDD@manganese dioxide composite active layer by spray sintering.

[0012] This invention also discloses the application of a titanium-based composite anode as the anode in the electrochemical preparation of high-purity manganese. In the electrochemical preparation of high-purity manganese, the titanium-based composite anode serves as the anode, a stainless steel plate as the cathode, and the current density for electrochemical preparation of high-purity manganese is 400~800 A / m. 2 .

[0013] Furthermore, in the electrochemical preparation system for high-purity manganese, the electrolyte is Mn 2+ The concentration is 35~45g / L, the concentration of (NH4)2SO4 is 80~120g / L, and the pH value is 7.0~8.5.

[0014] The beneficial effects of this invention are as follows: Compared with the prior art, the titanium-based composite anode of this invention consists of, from the inside out, a titanium substrate (Ti), an antimony tin oxide (ATO) underlayer, a BDD@manganese dioxide composite active layer, and a silicon isolation layer. The antimony tin oxide underlayer primarily serves two purposes: first, to improve the adhesion between the active layer and the substrate; and second, to prevent corrosion and passivation of the titanium substrate. The BDD@manganese dioxide composite active layer mainly aims to improve the oxygen evolution activity of the anode active layer, thereby reducing the anode working tank pressure. The silicon isolation layer primarily reduces corrosion of the active layer and prevents manganese dioxide deposition in the solution, maintaining electrode activity. The titanium-based composite anode improves the conductivity of the anode product, extends its service life, avoids lead contamination, and features a simple, easy-to-implement, and cost-effective manufacturing process.

[0015] Laser cleaning machines are used to treat the oxide scale on titanium substrates, replacing the traditional sandblasting and acid washing processes, making the process simple and practical. For the first time, vacuum deposition is introduced into the electrode to prepare an ATO underlayer, which significantly improves the conductivity. The voltage of the anode tank with the ATO underlayer is 4.2V, while the voltage of the anode tank without the ATO underlayer is 5.0V. The active layer is prepared using spraying technology, which has good uniformity.

[0016] The prepared titanium-based composite anode was applied to the electrochemical preparation of high-purity manganese, which solved the problem of easy corrosion of the anode in electrolysis, extended its service life (doubled the service life), and improved the purity of metallic manganese (content 99.99%). Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the structure of the titanium-based composite anode provided by the present invention.

[0018] Figure 2 The surface morphology diagram of the titanium-based composite anode provided by the present invention is shown.

[0019] Among them, 1-titanium substrate; 2-tin antimony oxide bottom layer; 3-BDD@manganese dioxide composite active layer; 4-silicon isolation layer. Detailed Implementation

[0020] The present invention will be further illustrated below with specific embodiments. However, these examples are for illustrative purposes only and are not intended to limit the scope of the invention.

[0021] The titanium-based composite anode of the present invention, see [reference]. Figure 1 The system includes a titanium substrate 1, on the surface of which, from the inside out, are a tin-antimony oxide underlayer 2, a BDD@manganese dioxide composite active layer 3, and a silicon isolation layer 4. The active layer is a BDD and manganese dioxide composite active layer. The thickness of the tin-antimony oxide underlayer 2 is 1 μm.

[0022] The method for preparing the titanium-based composite anode of the present invention includes the following steps: Step 1) Surface pretreatment of titanium substrate: Laser treatment is performed on titanium substrate 1 to form a uniform surface free of oxide scale; Step 2) A tin-antimony oxide underlayer 2 is prepared on the laser-treated titanium substrate 1 in Step 1 using a vacuum deposition method; the thickness of the tin-antimony oxide underlayer 2 is 1 μm. Step 3) Spray the active layer precursor onto the tin-antimony oxide base layer 2 prepared in step 2), and sinter to prepare a BDD and manganese dioxide composite active layer.

[0023] Step 4) Prepare a silicon isolation layer 4 on the BDD@manganese dioxide composite active layer 3 prepared in step 3).

[0024] Among them, the specific process of preparing the tin-antimony oxide underlayer 2 by vacuum deposition in step 2) is as follows: vacuum deposition is carried out by vacuum evaporation or magnetron sputtering.

[0025] The vacuum evaporation process involves evaporating a tin-antimony alloy using a resistance-heated quartz glass boat. The heating temperature of the evaporation source is 800-1000℃, oxygen is used as the reactant gas, and the system vacuum level is 10. -3 Pa, the distance from the evaporation source to the titanium sheet is 20~25cm.

[0026] The magnetron sputtering process is as follows: ATO target material is sputtered by DC magnetron in an argon atmosphere, with an argon gas pressure of 0.2~3Pa, a DC sputtering current of 80~120mA, and a DC sputtering voltage of 200~320V.

[0027] The specific process of step 3) is as follows: the tin-antimony oxide underlayer prepared in step 2) is sprayed with an active layer precursor, and then sintered to prepare a BDD@manganese dioxide composite active layer. The tin-antimony intermediate layer precursor solution is coated using a spraying technique, with one coat followed by one sintering. The sintering temperature is 200~450℃, and the holding time is 15~60min. This process is repeated multiple times, generally 5 times, depending on the designed active layer thickness.

[0028] The spraying method is either two-fluid spraying or roller coating. The process parameters for two-fluid spraying are: compressed air pressure of 0.5MPa, working speed of 2000mm / min~3000mm / min, spray width of 20.0cm, and liquid supply flow rate of 10.0mL / min~30.0mL / min.

[0029] The specific process of step 4) is as follows: a silicon isolation layer is prepared on the BDD@manganese dioxide composite active layer prepared in step 3).

[0030] The titanium-based composite anode prepared according to the above method was used as the anode for the electrochemical preparation of high-purity manganese. A stainless steel plate was used as the cathode, fixed in the electrolytic cell, and an electrodeposition current density of 400A~800A / m was applied. 2 .

[0031] In the electrochemical preparation system of high-purity manganese, the electrolyte is Mn 2+ The concentration is 35~45g / L, the concentration of (NH4)2SO4 is 80~120g / L, and the pH value of the electrolyte is in the range of 7~8.5.

[0032] Regarding the above technical solution, several preferred embodiments are described in detail below. Example

[0033] The preparation method of titanium-based composite anode includes the following steps: Step 1) Use a handheld laser cleaning machine to treat the surface of the titanium substrate, remove the surface oxide scale, and make the surface of the titanium substrate uniform.

[0034] Step 2): The laser-treated titanium substrate from Step 1) is used to prepare a tin-antimony oxide underlayer using vacuum evaporation. A quartz glass boat heated by resistance is used to evaporate the tin-antimony alloy. The heating temperature of the evaporation source is 800℃, oxygen is used as the reactant gas, and the system vacuum degree is 10. -3 Pa, the distance from the evaporation source to the titanium sheet is 25 cm, and the thickness of the ATO underlayer prepared by vacuum evaporation is 2 μm.

[0035] Step 3) The tin-antimony oxide substrate prepared in Step 2) is sprayed with the active layer precursor, and then sintered to prepare the BDD@manganese dioxide composite active layer. The active layer precursor solution is coated using a spraying technique, with one coat sprayed and one sintering. The sintering temperature is 350℃, and the holding time is 1 hour. The spraying and sintering process is repeated 5 times.

[0036] The specific process parameters for two-fluid spraying are: carrier gas pressure 0.3MPa, working speed 2500mm / min, spraying width 20.0cm, and liquid supply flow rate 10.0mL / min.

[0037] Step 4) Prepare a silicon isolation layer on the BDD@manganese dioxide composite active layer prepared in step 3), sinter at 350℃, hold for 1 hour, sinter once, and the thickness of the silicon isolation layer is 10μm.

[0038] The above preparation method can yield a titanium-based composite anode material Ti / ATO / BDD@MnO2 / SiO2 with excellent conductivity and long lifespan, and its surface morphology is as follows. Figure 2 As shown.

[0039] The titanium-based composite anodes prepared in steps 1) to 4) above were used for the electrochemical preparation of high-purity manganese. Specific operating procedures: The titanium-based composite anode (Ti / ATO / BDD@MnO2 / SiO2) and the stainless steel cathode were respectively fixed in the electrolytic cell, and an electrodeposition current density of 400 A / m was applied. 2 .

[0040] The electrolyte in the electrochemical preparation system of high-purity manganese contains: Mn 2+ The concentration of the electrolyte is 40 g / L, the concentration of (NH4)2SO4 is 100 g / L, and the pH value of the electrolyte is 7.5.

[0041] The above-mentioned Ti / ATO / BDD@MnO2 / SiO2 anode electrochemical preparation of high-purity manganese solves the disadvantage of easy corrosion of the anode in electrolysis, ensures the precipitation of high-purity metallic manganese, and avoids the generation of lead-containing anode sludge.

[0042] The titanium-based composite anode of this invention improves the adhesion between the active layer and the substrate while preventing corrosion and passivation of the substrate by adding a tin-antimony oxide underlayer. The composite active layer primarily enhances the oxygen evolution activity of the anode active layer, thereby reducing the working tank pressure of the anode. The silicon isolation layer mainly reduces corrosion of the active layer and prevents manganese dioxide deposition in the solution. Therefore, the titanium-based composite anode exhibits excellent electrical conductivity and a long service life.

[0043] The above embodiments are only used to illustrate the present invention and are not intended to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions also fall within the scope of the present invention, and the patent protection scope of the present invention should be defined by the claims.

Claims

1. A green titanium-based composite anode, characterized in that: The material includes a titanium substrate, on the surface of which, from the inside out, are a tin-antimony oxide underlayer, a BDD@manganese dioxide composite active layer, and a silicon isolation layer; the active layer includes two active substances, BDD and manganese dioxide.

2. The green titanium-based composite anode as described in claim 1, characterized in that: The thickness of the tin-antimony oxide underlayer is 0.5~4μm; the thickness of the silicon isolation layer is 4~20μm.

3. The method for preparing a green titanium-based composite anode as described in claim 1, characterized in that, Includes the following steps: Step 1) Perform surface treatment on the titanium substrate; Step 2) Deposit a tin-antimony oxide underlayer on the titanium substrate surface after the treatment in Step 1); Step 3) Prepare a BDD@manganese dioxide composite active layer on the tin-antimony oxide substrate prepared in Step 2); Step 4) Prepare a silicon isolation layer on the BDD@manganese dioxide composite active layer prepared in step 3).

4. The method for preparing a green titanium-based composite anode as described in claim 3, characterized in that: In step 1), a laser is used to treat the surface of the titanium substrate to make the surface of the titanium substrate uniform and free of oxide scale.

5. The method for preparing a green titanium-based composite anode as described in claim 3, characterized in that: In step 2), a tin-antimony oxide underlayer is prepared by vacuum deposition; the vacuum deposition method is either vacuum evaporation or magnetron sputtering.

6. The method for preparing a green titanium-based composite anode as described in claim 3, characterized in that: In step 3), a BDD@manganese dioxide composite active layer is prepared by spraying BDD and manganese-based precursors; wherein, spraying is performed once, sintering is performed once, and spraying and sintering are repeated multiple times until the required thickness of the BDD@manganese dioxide composite active layer is achieved.

7. The method for preparing a green titanium-based composite anode as described in claim 6, characterized in that: In step 3), a manganese nitrate solution containing BDD is used as a precursor. After spraying, it is dried at a temperature of 80~150℃ and then sintered at 200~450℃ for 15~60 minutes. The spraying method is two-fluid spraying or roller coating.

8. The method for preparing a green titanium-based composite anode as described in claim 3, characterized in that: In step 4), a silicon isolation layer is prepared on the BDD@manganese dioxide composite active layer by spray sintering.

9. The application of the titanium-based composite anode as described in claim 1 or 2 as an anode in the electrochemical preparation of high-purity manganese, characterized in that, In the electrochemical preparation of high-purity manganese, the titanium-based composite anode is used as the anode, the stainless steel plate is used as the cathode, and the current density for electrochemical preparation of high-purity manganese is 400~800 A / m. 2 .

10. The application as described in claim 9, characterized in that, In the electrochemical preparation system for high-purity manganese, the electrolyte is Mn 2 + The concentration is 35~45g / L, the concentration of (NH4)2SO4 is 80~120g / L, and the pH value is 7.0~8.5.